Synodalität: philosophische Überlegungen zum "Weg" der Kirche in der Zeit - Hünermann, Peter (Theologische Quartalschrift, 2012)
The article "Synodality: Philosophical Reflections on the 'Path' of the Churches in Time" first sketches the post-conciliar development of the theological concept of synodality. The author then draws on the most recent development of phenomenological-transcendental thinking to uncover the inner dimensions of synodality. Phenomenological-transcendental thinking was already present at Vatican II in an incipient version that still had onto-theological overtones. It unfolded in the post-conciliar period, beginning around 1970, in a new philosophical pre-understanding of God as unconditional freedom which the human being can and should anticipate in his or her behavior in the realm of freedom. In the subsequent course of the article the transcendental correlation between recognition and identity of the human being is discussed so that, based on this understanding, synodality appears to be an eschatological recognition to be realized at all levels of being the church and a believing acquistion of identity. Übersetzung: Martha M. Matesich